“Would You Like Some Victorian Dressing with That?” - Stetz, Margaret (Romanticism and Victorianism on the Net, 2009)
AbstractThis article challenges scholars to look beyond conventional audiences for Victorian studies and to go beyond conventional subjects, into the world of Victorian and Neo-Victorian fashion. It holds up the career of Dr. Valerie Steele, Director of the Museum at the Fashion Institute of Technology, as a model for how to conduct historical research into Victorian clothing and how to bring the results of that research to a broader public. It encourages academics to use the Internet to connect with a non-academic public that is already engaged with the Victorians through the medium of clothing, and it urges readers in general to see Neo-Victorian “mashup” dressing as an opportunity for serious exchange of knowledge about nineteenth-century culture.